2011
DOI: 10.1007/s11166-011-9123-3
|View full text |Cite
|
Sign up to set email alerts
|

Risky investment decisions: How are individuals influenced by their groups?

Abstract: We investigate the effect of group versus individual decision-making in the context of risky investment decisions in which all subjects are fully informed of the probabilities and payoffs. Although there is full information, the lottery choices pose cognitive challenges so that people may not be sure of their expected utility-maximizing choice. Making such decisions in a group context provides real-time information in which group members can observe others' choices and revise their own decisions. Our experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 37 publications
4
43
3
Order By: Relevance
“…Our experiment extends past research on the effect of a group environment on individual attitude to risk and ambiguity (Harrison et al 2007;Masclet et al 2009 ;Curley et al 1986, Trautman et al 2008, Viscusi et al 2011. We observe that individuals who are part of a group (whatever the decision rule) are i) significantly averse to risk, but ii) tend to be less risk averse than when they are alone; and iii) are averse to ambiguity and iv) tend to be more averse to ambiguity than when they are alone.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our experiment extends past research on the effect of a group environment on individual attitude to risk and ambiguity (Harrison et al 2007;Masclet et al 2009 ;Curley et al 1986, Trautman et al 2008, Viscusi et al 2011. We observe that individuals who are part of a group (whatever the decision rule) are i) significantly averse to risk, but ii) tend to be less risk averse than when they are alone; and iii) are averse to ambiguity and iv) tend to be more averse to ambiguity than when they are alone.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…A growing literature in economics precisely attempts at better understanding how individuals make decisions in a group environment (Harrison et al 2007;Masclet et al 2009;Viscusi et al 2011). Importantly, this literature differs from the literature on group decision making, which focuses on situations where a whole group makes a unique decision after deliberation (Blinder and Morgan 2005;Kocher et al 2006;Baker et al 2008;Shupp and Williams 2008;Ambrus et al 2009;Sheremata and Zhang 2010;Deck et al 2012;Zhang and Casari 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In both treatments, risk is found to play a role in the decision to (dis)invest in irrigation technology. However, it is surprising that risk averse farmers invest earlier, which is contradictory to our expectation that higher levels of individual risk aversion lead to later investment (Viscusi et al 2011). A possible explanation for this behaviour may be that more risk averse farmers consider irrigation as a risk management instrument and, therefore, invest earlier than the less risk averse farmers.…”
Section: Test Of H2 'Learning Effect' and H3 'Farmer-specific Effects'contrasting
confidence: 86%
“…Abdellaoui et al (2008) also found weakly concave utility in combination with weakly prevailing risk seeking for losses. Viscusi et al (2011) showed that observations of other people's choices do influence own decisions even when the own risks are fully known, so that the choices of the other people are not informative. This effect can play a role in our experiment if the experts' information is taken as reflecting the experts' decisions.…”
Section: Summary and Discussion Of Results Of Experiments Amentioning
confidence: 99%